2016
DOI: 10.1007/s10499-016-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of bovine lactoferrin as adjuvant for the modulation of the specific immune response in rainbow trout (Oncorhynchus mykiss W.)

Abstract: The present experiment was carried out in order to evaluate the potential\ud adjuvant effect of bovine lactoferrin (bLF) in modulating the specific antibody (Ab)\ud response to an exogenous protein, the human-c-globulins (HcG), injected intraperitoneally\ud in rainbow trout Oncorhynchus mykiss (Walbaum 1792). Moreover, serum natural antibody\ud (NatAb) level, serum total immunoglobulin (IgM) level and specific Ab response to\ud bLF were also analysed. Experimental data showed that HcG is able to stimulate a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Further studies have demonstrated that lactoferrin has bactericidal effect only when in its iron-free state and that iron-saturated lactoferrin has a reduced antimicrobial activity [222]. Lactoferrin has been widely reported for its application as an adjuvant to improve cellular immune responses of fish [223,224,225]. However, few studies are available on its use in fish preservation.…”
Section: Natural Preservatives For Fishmentioning
confidence: 99%
“…Further studies have demonstrated that lactoferrin has bactericidal effect only when in its iron-free state and that iron-saturated lactoferrin has a reduced antimicrobial activity [222]. Lactoferrin has been widely reported for its application as an adjuvant to improve cellular immune responses of fish [223,224,225]. However, few studies are available on its use in fish preservation.…”
Section: Natural Preservatives For Fishmentioning
confidence: 99%
“…Interestingly, bLF applied intraperitoneally led to improvement in the immune system, which was reflected in phagocyte stimulation (Cecchini et al., 2005). Later, Cecchini and Caputo (2017) used bLF (50 µg) in an immunization protocol via intraperitoneal injection with or without human‐γ‐globulins and Freund's complete adjuvant (FCA). The antibody response was measured at 20 and 40 days after immunization, which revealed that the combination of bLF‐soluble and human‐γ‐globulin antigens induces higher antibody production, even when compared with other adjuvants, such as FCA.…”
Section: Features Of Blfmentioning
confidence: 99%
“…Recent studies have detected a relationship between iron transporter glycoproteins and Salmo salar susceptibility to pathogens [57,58]. In salmonids, an iron transporter glycoprotein has been identified as a vaccine enhancer [59]. In vertebrates, it has been shown that iron transporter glycoproteins exert antibiofilm therapeutic [60,61] and antimicrobial activity by binding to iron, thereby preventing its use by bacteria [61][62][63][64] and thus causing alterations in the bacterial wall and, ultimately, death.…”
Section: Alternative Antibiotic Treatment In Salmon Farmingmentioning
confidence: 99%